Snails promote methane release from a freshwater lake ecosystem - Xu, Xiao; Zhao, Wei; Xiao, Ming; Huang, Jingxin; Fang, Changming; Li, Bo; Nie, Ming (Frontiers in Environmental Science, 2014)
Benthic fauna, as ecosystem engineers, can strongly affect microbial-driven ecosystem biogeochemical cycling. However, the effects of benthic fauna, especially epifauna, on CH4 cycling remain still elusive. In this study, CH4 effluxes were both measured along a gradient of snail density in a freshwater lake ecosystem in China, and monitored in manipulated laboratory microcosms with and without snails. Field CH4 efflux was significantly increased with snail density. Likewise, the stimulating effects of freshwater snails on CH4 effluxes were evident in the homogenised indoor microcosms. These results show that snails can stimulate CH4 efflux in the freshwater lake ecosystem. Moreover, the average efflux of CH4 emitted from snails’ habitats has reached 15.33 mg CH4-C m-2 d-1. By comparing with those emitted from vegetated coastal marsh and alpine wetland, this data indicates that snails’ habitats are strong sources of CH4 in a freshwater ecosystem. This study suggests identifying and modeling epifauna activity as a function of CH4 cycling could improve the mechanistic understanding of wetland biogeochemical cycling responses to climate change.